Nutrient dynamics in tea (Camellia sinensis L.) based shaded perennial agroforestry system in Western ghats, Kerala - Niranjana, K.S.; Viswanath, S. (Indian Journal of Agroforestry, 2020)
The contribution made by different components of nutrient cycling like litterfall, tree loppings, stemflow and throughfall to soil nutrient pool and the factors influencing the same were studied in Grevillea robusta (Silver oak) shade tree in tea estates situated in Western ghats of Munnar, Kerala. The total annual litter production by Grevillea was 4150 kg ha-1 yr-1, which was influenced by weather parameters and physico-chemical properties of soil. The Grevillea trees added, on an average, 75.15 kg N ha-1 yr-1, 41.19 kg K ha-1 yr-1 and 3.51 kg P ha-1 yr-1 towards soil nutrient pool in the form of litterfall, loppings, throughfall and stemflow. Of the total nutrients added, maximum contribution was from litterfall, which was 61% of total N, 74% of P and 38% of K. The corresponding contribution from loppings were 12% of total N, 11% P and 21% K. Although loppings of Grevillea added significant quantities of biomass to the soil, its contribution to soil nutrient pool was relatively low when compared to litterfall. Loppings yielded very low phosphorus (0.40 kg ha-1 yr-1) moderate amount of N (9.07 kg ha-1 yr-1) and K (7.73 kg ha-1 yr-1) to soil nutrient pool which corresponded to 12%, 11% and 19% of total N, P and K added annually to soil nutrient pool. Even though the concentration of nutrients in stemflow and throughfall was high, its contribution towards the total soil nutrient pool was low.